Analisis dan Mitigasi Emisi Gas Buang Akibat Transportasi (Studi Kasus Kabupaten Magetan) - Purnomoasri, RA Dinasty; Handayani, Dewi (ENVIRO: Journal of Tropical Environmental Research, 2022)
The Intergovernmental Panel Climate Change (IPCC) states that transportation contributes 13.1% of emissions (IPCC, 2006). Magetan Regency plans to support Indonesia in reducing emissions by 20% by 2040 by analysing and mitigating greenhouse gas (GHG) emissions generated by the transportation sector. The analysis was conducted by calculating greenhouse gas (GHG) emissions based on traffic volume survey data and calculating the fuel oil (BBM) used to obtain the amounts of emissions generated. From the analysis, it was found that CO2 emissions generated by the transportation sector in Magetan Regency amounted to 3,105,318.08 tons/year in 2020 and had the potential to increase by 3.31% per year. As mitigation actions, three activities are proposed, namely the use of public transportation, the movement of walking to school and greening. From the three actions, the total emissions are expected to be reduced by 1,422,516 tons/year or equivalent to 45% reduction of total emissions if the three proposed activities are implemented. If this is implemented, Magetan Regency will be able to contribute 0.22% of GHG emission reduction by 2040. If all districts in Indonesia also implement this mitigation, the transportation sector will contribute 9.15% of the emission reduction in Indonesia in 2040.